Pendampingan Perakitan TTG Mesin Penetas Telur Untuk Komunitas Peternak Ayam Kampung Pringsewu Lampung - Sally Cahyati; Rosyida Permatasari; Pudji Astuti; Triwulandari (CV. Multi Kreasi Media, 2023)
The demand for local chicken meat supply in Lampung is relatively high, but it cannot be fully met now. Chicken farmers, who are the suppliers of local chicken meat, face difficulties due to the fluctuating supply of chicks for traditional chicken farming. The success rate of traditional chicken hatching is only around 50%, which necessitates the use of egg incubators to condition eggs in an ideal environment for hatching, thus minimizing hatching failures. The machine works by maintaining a consistent temperature in the incubation room throughout the hatching process, periodically rotating the eggs in four positions, and is equipped with temperature and humidity monitoring devices. In the Community Service Program (PkM), the approach used is a mentoring method, allowing farmers to ask questions directly if they encounter difficulties. The expected outcome is that chicken farmers will be able to assemble egg incubators independently, creating the egg-turning mechanism and the machine's casing, while other control and support tools will be purchased. During the mentoring process, farmers will be provided with working drawings for the driving mechanism, machine casing, and specifications of the necessary tools and materials. Farmers will also receive a step-by-step guide for assembly, making it easy to follow. At the end of the PkM, it is expected that farmers will have a minimum understanding of 90%-100 % of what was taught during the mentoring process, and for any remaining questions, they can consult online or through discussions on WhatsApp.